Diagnostic and Therapeutic Approach in a Metastatic Vaginal Adenocarcinoma: A Case Report - Egger, Eva Katharina; Ralser, Damian J.; Lindner, Kira; Recker, Florian; Marinova, Milka; Savchenko, Oleksandre; Lau, Jan-Frederic; Mustea, Alexander (Frontiers in Immunology, 2021)
Background: Vaginal Adenocarcinomas (VAC) are most often reported after intrauterine exposition to Diethylstilbestrol. Rarely, VACs are reported as a malignant transformation of vaginal adenosis or endometriosis, in the context of chromosomal abnormalities or malformations of the uterus or the vagina. VACs without DES exposition have a poor prognosis and a significantly worse outcome compared to vaginal squamous cell carcinomas or DES associated VACs. Objective: Here, we report the case of a primarily metastatic VAC, treated successfully with different lines of chemo-, antiangiogenic-, antibody- and immunotherapy. Case: The 49 year old patient presented in 5/2018 with a primarily pulmonary metastatic vaginal adenocarcinoma (VAC). Significant tumorreduction was seen after 6 cycles of Carboplatin/Paclitaxel/Bevacizumab. Bevacizumab maintenance therapy and later Cisplatin mono led to local and distant tumor progression. To identify a potential targeted therapy, new tumor biopsies were obtained. Immunohistochemistry revealed a ERBB2 expression and Paclitaxel weekly plus Trastuzumab q3w was administered. Due to local and pulmonal tumorprogression after six months and persistent ERBB2 positivity, the therapy was adjusted to trastuzumab emtansine (T-DM1) but the patient remained progressive after 3 cycles of T-DM1 showing a new bone metastasis. The new tumor biopsies revealed a combined positive Score (CPS) of 2 regarding PD-L1 and Pembrolizumab 200 mg q3w was initiated. The bone metastasis was radiated and treated with Denosumab. Extreme tumor regression followed by stable disease was maintained for 9 month. Due to a slow locoregional progress only with new inguinal lymphnode and pararectal lymphnode metastases a new tumor biopsy was taken. Molecular profiling showed an ARID1A mutation, a mutational burden of 5.1 mutations per megabase and no genfusions. Based on these findings, therapy with PD-L1 antibodies, PD-1 antibodies, gemcitabine or Dasatinib was suggested. Therefore, administration of Pembrolizumab was continued and local radiation therapy was performed. This led to a decrease in local tumor manifestations and a stable systemic disease. Conclusion: Our case demonstrates the diagnostic and therapeutic approach in a patient with primary metastatic vaginal adenocarcinoma. By tumorgenetic profiling, different lines of systemic therapy including antiangiogenic therapy, monoclonal antibody therapy, immunotherapy and local radiation therapy were identified and successfully administered.